The Impact of Financial Literacy, Technological Progress, Income, and Lifestyle on Investment Interest: The Role of Gender as a Moderator Variable - Erny Luxy D Purba; Roza Thohiri; Kornelius Harefa (Owner : Riset dan Jurnal Akuntansi, 2025)
Along with the development of the global economy and changing financial trends, students are increasingly faced with opportunities to get involved in various investment instruments. Therefore, students are potential young investors who are expected to be able to contribute actively to advancing and increasing investment. This research aims to examine and describe the factors that influence students' investment interest in the city of Medan. This research was conducted at economics faculties at six universities in Medan City. The data source for this research is a primary data source. This research uses a quantitative approach. The sample for this research consisted of 262 data which met the sample criteria using the purposive sampling method. The data obtained was then analyzed using Partial Least Square-SEM with the help of the smartPLS 4.0 application. Partial research results show that financial literacy, technological progress, income have a positive and significant effect on investment interest, lifestyle does not have a significant effect on investment interest. The moderating variable gender does not act as a moderating variable that strengthens or weakens the relationship between Financial Literacy and Investment Interest. Gender as a moderating variable further strengthens the relationship between Technological Progress and Investment Interest. The gender moderating variable does not influence the relationship between Income and Investment Interest. Gender as a moderating variable does not strengthen or weaken the relationship between Lifestyle and Investment Interest. It is hoped that this research can provide additional contributions in the field of similar literature for the development of further research and be useful for interested parties.